A Fruitful Endeavor: Scent Cues and Echolocation Behavior Used by Carollia castanea to Find Fruit. Issue 1 (11th March 2020) - Leiser-Miller, L B; Kaliszewska, Z A; Lauterbur, M E; Mann, Brianna; Riffell, J A; Santana, S E
Synopsis: Frugivores have evolved sensory and behavioral adaptations that allow them to find ripe fruit effectively, but the relative importance of different senses in varying foraging scenarios is still poorly understood. Within Neotropical ecosystems, short-tailed fruit bats ( Carollia : Phyllostomidae) are abundant nocturnal frugivores that rely primarily on Piper fruits as a food resource. Previous research has demonstrated that Carollia employs olfaction and echolocation to locate Piper fruit, but it is unknown how their sensory use and foraging decisions are influenced by the complex diversity of chemical cues that fruiting plants produce. Using free-ranging C. castanea and their preferred food, Piper sancti-felicis, we conducted behavioral experiments to test two main hypotheses: (1) foraging decisions in C. castanea are primarily driven by ripe fruit scent and secondarily by vegetation scent, and (2) C. castanea re-weights their sensory inputs to account for available environmental cues, with bats relying more heavily on echolocation in the absence of adequate scent cues. Our results suggest that C. castanea requires olfactory information and relies almost exclusively on ripe fruit scent to make foraging attempts. Piper sancti-felicis ripe fruit scent is chemically distinct from vegetation scent; it is dominated by 2-heptanol, which is absent from vegetation scent, and has a greater abundance of β-caryophyllene, β-ocimene, γ-elemene, and α-cubebene. Although variation in echolocation call parameters was independent of scent cue presence, bats emitted longer and more frequent echolocation calls in trials where fruit scent was absent. Altogether, these results highlight the adaptations and plasticity of the sensory system in neotropical fruit bats.